NOT JUST TYPE 2 DIABETES: SEVERE INSULIN RESISTANCE WITH ATYPICAL FAT DISTRIBUTION SUGGESTS LIPODYSTROPHY SYNDROME - Lee, Qin Zhi; Tee, Hwee Ching; Ho, Jin Hui (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Lipodystrophy syndromes are rare disorders of adipose tissue distribution, often leading to severe insulin resistance and metabolic complications. We present a case of a young woman initially diagnosed with type 2 diabetes, unresponsive to standard insulin therapy, who was ultimately diagnosed with familial partial lipodystrophy (FPLD). CASE A 26-year-old female, with diabetes diagnosed 4 years ago, was referred for uncontrolled capillary blood glucose levels persistently ranging from 20–25 mmol/L despite high-dose basal-bolus insulin and oral hypoglycemic agents. Her body mass index (BMI) was 22 kg/m² with an HbA1c of 12.2%. Autoantibody screening (GAD, ICA, IA2 antibodies) was negative, and C-peptide was markedly elevated (2193 pmol/L). Her metabolic profile showed hypertriglyceridemia, raised liver enzymes suggestive of metabolic-dysfunction associated steatotic liver disease, proteinuria due to diabetic kidney disease, and oligomenorrhea. She had a well-defined muscular appearance in her limbs with prominent veins, raising suspicion of partial lipodystrophy. Fat loss was noted in the trunk, hips, and gluteal regions, contrasting with fat accumulation in the face, neck, and viscera. Mild acanthosis nigricans were present, but there was no significant hirsutism. She denied antiretroviral therapy use and autoimmune features were absent. While her family history was unremarkable for diabetes or consanguinity, her mother had died from renal failure at the age of 40. She acknowledged a distinct body habitus compared to her siblings. Whole-exome sequencing confirmed the presence of a heterozygous pathogenic p.Arg482Trp variant in the LMNA gene, diagnostic of autosomal dominant FPLD type 2. Her management included increased insulin doses and the addition of pioglitazone to enhance adiponectin levels and insulin sensitivity. CONCLUSION This case highlights the need to consider lipodystrophy syndromes in young patients with severe insulin resistance and atypical fat distribution. Early diagnosis enables targeted therapy and better metabolic control.